2010
DOI: 10.1007/s00127-010-0321-0
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms among immigrants and ethnic minorities: a population based study in 23 European countries

Abstract: Purpose European studies about ethnic inequalities in depressive symptoms are scarce, show inconclusive results and are complicated by the discussion of what constitute (im)migrant and ethnic minority groups. Moreover, comparisons across countries are hampered by a lack of comparable measures of depressive symptoms. This study aims to assess the prevalence and determinants of depressive symptoms among immigrants, ethnic minorities and natives in 23 European countries. Methods Multilevel analyses are performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
145
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(177 citation statements)
references
References 74 publications
(43 reference statements)
10
145
0
7
Order By: Relevance
“…It is expected that by 2030, depression will be the second most disabling disorder worldwide (6). However, prevalence rates of depression vary considerably among racial-ethnic minority populations and nonminority native-born people (7). Socioeconomic conditions of and discrimination toward racial-ethnic minority groups have been found to be important predictors of these differences.…”
mentioning
confidence: 99%
“…It is expected that by 2030, depression will be the second most disabling disorder worldwide (6). However, prevalence rates of depression vary considerably among racial-ethnic minority populations and nonminority native-born people (7). Socioeconomic conditions of and discrimination toward racial-ethnic minority groups have been found to be important predictors of these differences.…”
mentioning
confidence: 99%
“…44 In sum, this study has shown that discrimination against individuals with a visual impairment in the rental housing market is substantial, among both private landlords and real estate agents. Given that discrimination has a negative effect on both physical and mental health 26,27,28,29 , this finding should urge health researchers to devote more attention to social causes of health problems among individuals with an impairment. …”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…There is compelling evidence that discrimination has profound negative effects on both mental and physical health. 26,27,28,29 The detrimental effects may occur through the mechanisms of stress responses and adapted health behaviours. 28 Given these profound health consequences, it is remarkable that discrimination of people with a disability is so little examined.…”
Section: Introductionmentioning
confidence: 99%
“…Dat etnische minderheidsgroepen gemiddeld genomen een lager opleidingspeil hebben en een slechtere positie op de arbeidsmarkt bekleden, verklaart dan ook ten dele de relatief hoge prevalentie van psychische klachten. Toch blijven de verschillen geprononceerd, zelfs nadat men hier rekening mee houdt (Aichberger e.a., 2010;Missine & Bracke, 2012;De Wit e.a., 2008;Van der Wurff e.a., 2004). Een mogelijk verklaring voor het relatief vaak voorkomen van psychische klachten zou volgens verschillende auteurs kunnen liggen in de acculturatie-ervaringen van migranten (Koneru e.a., 2007;De Wit e.a., 2008).…”
Section: Inleidingunclassified